Recent trends in Employees’ Earnings Inequality in Portugal. A quantitative analysis between 1986 and 2017 - Simões, Marta (2020)
This paper examines employees’ earnings inequality in Portugal for1986-2017 using data from the Personnel Records database. Our objective istwofold: (a) characterize earnings inequality by comparing representative distri-butions, before and after the great crisis; and (b) investigate the role played bythe business cycle on the behaviour of earnings inequality by estimating Auto-regressive Distributed Lag (ADL) models. To identify trends and variations along the trend in earnings inequality we use cardinal measures and the coefficient ofvariation. We inspect the characteristics of earnings distributions in terms of mo-ments (mean and median) and polarization (using relative distributions analysis).The main findings are: (1) earnings inequality shows a positive trend (exceptduring the great crisis); (2) polarization is present in every year, with lower po-larisation prevailing over upper polarization, both evolving at different paces(very fast 1989-2002; slower pace 2002-2008; negative growth 2008-2017); (3) the business cycle relationship with earnings inequality is negative.